The role of Saudi media in spreading awareness of corruption issues among university students (The International Journal of Educational Sciences and Arts, 2025)
Saudi media has achieved remarkable development in the modern era, becoming a key tool in shaping societal awareness and influencing public opinion, particularly on issues of national importance such as combating corruption. With the proliferation of digital and traditional media, it has become necessary to study the role of Saudi media in raising awareness of corruption issues among university students, as they are an influential group in the future of society. This research aims to analyze media strategies in promoting integrity and transparency and explore the extent to which media messages influence youth attitudes and behaviors toward corruption. The problem of the study is to analyze the role of Saudi media in raising university students' awareness of corruption issues and the extent of its influence in shaping their attitudes and behaviors toward this phenomenon. The objectives of the study include identifying the most influential media outlets, analyzing the role of media coverage, studying the impact of digital media and social media platforms, exploring the role of media figures in raising awareness, analyzing the impact of media campaigns on changing youth behaviors toward reporting corruption, and identifying the most prominent challenges facing the media in this area. The study results showed a moderate positive correlation between university students' exposure to Saudi media and their level of awareness of corruption issues. The correlation coefficient reached 0.52, with a statistical significance level of 0.001, reflecting the media's role in raising awareness. However, the study did not show a statistically significant relationship between the type of media outlet used and university students' awareness of the importance of combating corruption. The correlation coefficient reached 0.12, with a significance level of 0.06, indicating that the type of media outlet is not the primary factor shaping youth's perception of this issue. Recommendations: The study emphasized the need to intensify media coverage using methods that suit youth interests and produce diverse awareness-raising content such as investigative reports and talk shows. It also called for strengthening the role of digital platforms in raising awareness, designing interactive media campaigns, and encouraging investigative journalism to uncover corruption cases. It emphasized the importance of involving university students in media initiatives, promoting a culture of reporting corruption, and leveraging influential media professionals to disseminate awareness messages. It also emphasized developing information presentation methods using multiple media to ensure messages are delivered effectively. The study confirms that Saudi media plays an important role in raising awareness about corruption issues, but there is a need to develop media strategies to further enhance its influence in shaping university students' awareness and attitudes toward this important issue.
Keywords: Saudi Media; Community Awareness; Corruption; University Students; Integrity and Transparency